Anxiolytic activity of methanolic leaf extracts of Amaranthus cruentus Linn. and Rumex acetosa Linn. in mice - Chitra Govind Rajput; Sachinkumar Vasantarao Patil; Pallavi Abhijeet Patil (Journal of Applied Pharmaceutical Research, 2026)
Background: The current study aims to define the anti-anxiety properties of the leaves of Amaranthus cruentus Linn. and Rumex acetosa Linn. Methodology: Soxhlet extraction was used to extract the leaves of Rumex acetosa Linn and Amaranthus cruentus Linn. FTIR and GC-MS were used to investigate the fraction. The elevated plus maze test (EMPT) was used to assess the antianxiety property of methanolic extracts at 200 mg/kg and 400 mg/kg in Swiss albino mice. Results and discussion: Alkaloids, steroids, glycosides, amino acid flavonoids, carbohydrates, and phenolic tannins are found in both extracts. The percentage yields of petroleum ether, chloroform, and methanol extracts were 2.4%, 3.6%, and 10% for Amaranthus cruentus, and 2.1%, 3.2%, and 8% for Rumex acetosa, respectively. Amaranthus cruentus extracts were associated with significant increases (P < 0.05) in the amount of time and the number of entries in open arms. Open arm entries (p < 0.01) and time spent in the open arm (p < 0.01) were both increased by 200 mg/kg of Rumex acetosa Linn extract, while 400 mg/kg increased both of these variables (p < 0.001). Nevertheless, activity rises in tandem with the dosage of Rumex acetosa Linn extract. In EMPT, diazepam (2 mg/kg) significantly increased open arm entries (22.67) and time spent in open arms (3.273 min), while decreasing closed arm entries (6.33) and time spent in closed arms (1.582 min) compared to the control group, confirming its potent anxiolytic activity. Conclusion: The methanolic extracts of both plants exhibit significant anxiolytic properties.